Reducing acute kidney injury in pediatric oncology patients: An improvement project targeting nephrotoxic medications. Issue 8 (3rd June 2020) - Young, Jennifer; Dahale, Devesh; Demmel, Kathleen; O'Brien, Maureen; Geller, James; Courter, Josh; Haslam, David B.; Danziger‐Isakov, Lara; Goldstein, Stuart L.
Abstract: Background: Nephrotoxic medication exposure and associated acute kidney injury (AKI) occur commonly in hospitalized children. At Cincinnati Children's Hospital Medical Center, there is an initiative to increase awareness of nephrotoxic medication exposure and decrease rates of associated AKI. The oncology service utilized these data in a quality improvement project to drive reductions in AKI rates. Methods: Three interventions were implemented targeted at decreasing the incidence of nephrotoxic exposure, as well as protecting against the conversion of exposures to AKI episodes. Cefepime replaced piperacillin‐tazobactam for febrile neutropenia, vancomycin stewardship limited empiric courses to 72 hours, and nephroprotection for intravenous contrast administration was standardized for defined high‐risk patients. Results: The study cohort comprised 42 520 noncritically ill patient days admitted to the oncology service at Cincinnati Children's Hospital Medical Center. A total of 273 unique patients were exposed to combination nephrotoxic medications, leading to 111 AKI episodes. The rate of nephrotoxic medication exposure within the oncology service decreased by 49% from 16.08 to 8.17 per 1000 patient days. Episodes of AKI associated with nephrotoxic medication exposure decreased by 45% from 3.48 to 1.92 per 1000 patient days. Conclusion: Interventions to decrease AKI took a three‐pronged approach. Collectively, this approach was proven successful with significant reductions in both rates of nephrotoxic medication exposure and associated AKI among hospitalized oncology patients.